2020
DOI: 10.1111/cob.12405
|View full text |Cite
|
Sign up to set email alerts
|

Safety of bariatric surgery in patients with inflammatory bowel disease: A systematic review and meta‐analysis

Abstract: Summary The efficacy of bariatric surgery in achieving weight loss and preventing long‐term comorbidities such as cardiovascular diseases, diabetes mellitus and osteoarthritis is well established. Data regarding safety of bariatric surgery in patients with inflammatory bowel disease (IBD) is scarce. We attempted a systematic review and meta‐analysis to evaluate the complications following bariatric surgery in patients with IBD. The primary outcomes evaluated were wound infection, Clavien‐Dindo grade > II compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Few studies have investigated the effect of weight loss on the outcomes following surgery for IBD[ 57 ]. Bariatric surgery is one of the ways of treating obesity[ 68 ], but its use in IBD is limited because of the complexity of those diseases and the scarcity of studies to support the decision-making of health professionals[ 69 ]. Reviews of the impact of bariatric surgery on the clinical course of IBD found that it is relatively safe and reduces the risk of complications[ 69 , 70 ]; however, more robust original articles evaluating surgical outcomes must be added to the literature to increase the reliability of those findings.…”
Section: Nutritional Status and Postoperative Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have investigated the effect of weight loss on the outcomes following surgery for IBD[ 57 ]. Bariatric surgery is one of the ways of treating obesity[ 68 ], but its use in IBD is limited because of the complexity of those diseases and the scarcity of studies to support the decision-making of health professionals[ 69 ]. Reviews of the impact of bariatric surgery on the clinical course of IBD found that it is relatively safe and reduces the risk of complications[ 69 , 70 ]; however, more robust original articles evaluating surgical outcomes must be added to the literature to increase the reliability of those findings.…”
Section: Nutritional Status and Postoperative Complicationsmentioning
confidence: 99%
“…Bariatric surgery is one of the ways of treating obesity[ 68 ], but its use in IBD is limited because of the complexity of those diseases and the scarcity of studies to support the decision-making of health professionals[ 69 ]. Reviews of the impact of bariatric surgery on the clinical course of IBD found that it is relatively safe and reduces the risk of complications[ 69 , 70 ]; however, more robust original articles evaluating surgical outcomes must be added to the literature to increase the reliability of those findings. It should be noted that malnutrition is common in patients with IBD and that people with high BMIs may also have nutritional deficiencies[ 37 , 71 , 72 ].…”
Section: Nutritional Status and Postoperative Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Aziz et al reported a systematic review and meta-analysis which revealed the rates of wound infection, Clavien-Dindo grade > II complications and IBD exacerbation were 4.1%, 2% and 4.3%, respectively in addition to rate of mortality, stricture, small bowel obstruction, acute kidney injury (AKI) and venous thrombo-embolism were 0.1%, 6.5%, 6.7%, 2.2% and 0.1%, respectively. 30 In our study six patients (9.8%) discontinued their medications and eight patients (13.1%) had a reduction in the dosage of the medications (azathioprine and sulfasalazine). The mechanism likely due to mutual chronic inflammatory state between CD and obesity.…”
Section: Discussionmentioning
confidence: 50%
“…In 2020, systematic review and meta‐analysis included 10 studies reported by Ragat et al showed that the adverse events with SG was 21.6%, EWL and BMI reduction at 12 month after surgery was 66.1% and 13.7 kg/m 2 , respectively in addition to decrease, increase, and no change of IBD medications were 45.6%, 11%, and 57.6%, respectively 29 . Aziz et al reported a systematic review and meta‐analysis which revealed the rates of wound infection, Clavien‐Dindo grade > II complications and IBD exacerbation were 4.1%, 2% and 4.3%, respectively in addition to rate of mortality, stricture, small bowel obstruction, acute kidney injury (AKI) and venous thrombo‐embolism were 0.1%, 6.5%, 6.7%, 2.2% and 0.1%, respectively 30 . In our study six patients (9.8%) discontinued their medications and eight patients (13.1%) had a reduction in the dosage of the medications (azathioprine and sulfasalazine).…”
Section: Discussionmentioning
confidence: 99%